Bridging the Socio-Spatial and Digital Divide: Evaluating Smart City Governance and Bureaucratic Readiness in Emerging Metropolitan Regions - Sri Haryaningsih; Farah Devi Andriani; Parlindungan Parlindungan; Dita Purnama (Jurnal Restorasi : Hukum dan Politik, 2025)
The intersection of digital transformation and regional development often uncovers structural disparities known as the socio-spatial and digital divide. While smart city initiatives promise enhanced urban efficiency, their success depends heavily on bureaucratic readiness and inclusive governance frameworks. This study evaluates the dynamics of smart city governance and bureaucratic adaptability within a rapidly expanding metropolitan region. Utilizing a mixed-methods approach combining Structural Equation Modeling (SEM) and thematic qualitative analysis, this research measures institutional readiness, technological infrastructure, and inclusive policy delivery across diverse administrative tiers. The empirical findings indicate that bureaucratic inertia and centralized infrastructure significantly exacerbate the digital-spatial divide, limiting smart city benefits in peripheral areas. The study concludes that bridging this divide requires polycentric governance structures and localized capacity-building. This research provides a critical framework for public administrators and territorial planners navigating digital transitions in emerging economies.